Interannual variation in evapotranspiration in an urban forest reserve with respect to drought - Yang, Ruizhi; Liu, Peng; Tian, Yun; Ma, Jingyong; Bai, Yujie; Li, Cheng; Huang, Songyu; Mu, Yanmei; Hayat, Muhammad; Iqbal, Sundas; Yu, Haiqun; Zhang, Feng; et al. (Frontiers in Forests and Global Change, 2023)
A warming global climate is expected to perturb the hydrological cycle, resulting in deviations in both frequency and duration of drought, and thus being hypothesized to lead to interannual variation in evapotranspiration (ET). Interannual variation in ET in urban forest ecosystems in response to drought remains poorly understood. Here, ET in an urban-forest reserve in the Megalopolis of Beijing was investigated using eddycovariance measurements collected over six consecutive years (2012)(2013)(2014)(2015)(2016)(2017). Mean annual cumulative ET was 462±83 mm (± first standard deviation), with a coefficient of variation of 18%. Interannual variation in both annual and monthly ET was shown to be largely controlled by canopy conductance (gs), affected by environmental factors. Main factors affecting interannual variation in monthly ET varied seasonally, being soil volumetric water content (VWC) and normalized difference vegetation index (NDVI) in spring, precipitation and soil temperature in summer, and VWC and net radiation (Rn) in autumn. Interannual variation in annual ET was driven largely by spring and midsummer drought induced by insufficient precipitation during the non-growing and midgrowing season, respectively. Spring drought reduced annual ET through restricting leafing out and shortening growing season length (GSL), and reducing normalized difference vegetation index (NDVI). Summer drought reduced annual ET through reducing stomatal conductance. Results from this study point to the importance of precipitation timing and volume and soil moisture carry-over effect in controlling interannual variation in ecosystem ET. Irrigation during early spring and mid-summer is viewed as a practical management measure for sustaining growth and better ecosystem services in urban forests of northern China.